Freio de Ouro: The selection tool for Crioula breed Freio de Ouro como ferramenta de seleção na raça Crioula - Salles E.L.* (2016)
© 2016, Universidad de Cordoba,Servicio de Publicaciones. All rights reserved.The main equestrian test of the Crioula breed or Freio de Ouro is an important selection tool, which includes morphology evaluation as well as nine functional tests with or without the presence of cattle, which serves to test the horse ability to cattle handing and to help the country man in his daily work. This research has been developed given the economic and social importance of this breed and the lack of studies concerning equine genetics in our country. We collected information from the Freio de Ouro awards in all editions (1982-2014), as well as genealogy of prized animals back to their fifth generation. Further analyzes were performed in order to identify the influence of the main ancestors on Freio de Ouro results. It was observed that few stallions are founders of most of 165 awarded animals. The Freio de Ouro can be considered a selection tool because winning horses were the parents of some winning animals. The vast majority of the winning animals were born in Brazil, offspring to imported stallions and national mothers on some occasions. Some animals were awarded on more than one occasion, but none of them was able to repeat the first place.